Nature of science and chemistry education - Vesterinen, Veli-Matti (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
Nature of science (NOS) is widely recognized as one of the key aims of chemistry education. The purpose of this paper is to describe the importance of teaching NOS as well as to discuss the role of NOS in sustainable chemistry education.